WDM Photonic transmission system - Mohd Shafiq Mohammad Shater (School of Microelectronic Engineering, University Malaysia Perlis, 2011)
The aim of this project to design, simulate and analyse basic photonic transmission system. The idea is to vary transmission parameters such as data speed, distance and dispersion. The project plan consists of literature review, and familiarization of the software, and system development. In this project, the designs are based on single channel and two different transmission systems i.e. WDM and OTDM system. These two signals are transmitted into a long haul fibre system. It is expected to design a system which can transfer huge amount of data in long distance. The system is expected to transfer up to 420km in a single span. The project starts with a discussion on understanding and application of optical fibre technology in modern transmission system. The design and simulation are carried out using Optisystem software. This project contributes in two major aspects; diverse applications that give huge impact to society telecommunications and transmission system that have huge potential in photonics transmission systems especially high speed networks.